2010
DOI: 10.1038/onc.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2 stabilizes, but functionally inactivates p53 by binding to the cysteine 277 residue

Abstract: 15-Deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), a representative cyclopentenone prostaglandin, has many interesting biological effects. In this study, treatment of human breast cancer cells (MCF-7) with 15d-PGJ 2 led to accumulation of p53 protein. However, the p53 DNA binding and its transcriptional activity were significantly reduced. 15d-PGJ 2 directly modified p53 as verified by reacting recombinant p53 with biotinylated 15d-PGJ 2 . 9,10-Dihydro-15-deoxy-D 12,14 -prostaglandin J 2 lacking the electrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
(91 reference statements)
1
21
0
Order By: Relevance
“…These observations offer an additional possibility that CDDO and 15d-PGJ 2 could directly bind to the active site of a signaling molecule involved in the Akt pathway. One study has shown that biotinylated CDDO is capable of binding and thus inactivating the active site of PTEN [37], and 15d-PGJ 2 is capable of inhibiting the activities of proteins through direct covalent modification [51], [52]. Further studies involving biochemical approaches should help us understand the exact nature of action of compounds involving electrophilic carbon.…”
Section: Discussionmentioning
confidence: 99%
“…These observations offer an additional possibility that CDDO and 15d-PGJ 2 could directly bind to the active site of a signaling molecule involved in the Akt pathway. One study has shown that biotinylated CDDO is capable of binding and thus inactivating the active site of PTEN [37], and 15d-PGJ 2 is capable of inhibiting the activities of proteins through direct covalent modification [51], [52]. Further studies involving biochemical approaches should help us understand the exact nature of action of compounds involving electrophilic carbon.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the effect of 15d-PGJ 2 on GR SUMOylation and glucocorticoid-regulated gene programs. 15d-PGJ 2 has been shown to trigger cell signaling cascades via directly interacting with proteins containing reactive cysteine residues (29,30,36). 15d-PGJ 2 principally activates the NRF2 pathway by modifying KEAP1, the inhibitory partner of NRF2, which results in stabilization and increased chromatin binding of the NRF2 and activation of genes such as HMOX1 that are involved in the cytoprotection against oxidative stress (25,26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Cys277 has also been identified as a possible substrate for selenomethionine (SeMet)-dependent redox-regulation of p53 [15], and it has been postulated that the redox-state of Cys277 serves as a switch to activate DNA repair machinery [47]. Furthermore, an electrophilic cyclopentenone prostaglandin, 15-deoxy-Δ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), has been shown to bind to Cys277 in vivo, leading to an increase in p53 stability and reduction of its transcriptional activity [48]. Cys277 is located in the conserved p53 motif BOX-V (amino acid residues 272-288).…”
Section: Preferential Alkylation Of Cys182 and Cys277mentioning
confidence: 99%